Training needs of university teachers. - María Teresa Espinosa Martín (Universitat Politècnica de València, 2014)
The methodological and conceptual updates that occurred in the teachinglearning process that takes place in universities have been carried out since the entry into force of the European Higher Education Area (EHEA), imply changes in the different areas that make up the educational context : institutions, students and teachers. This educational framework requires the acquisition of certain skills, not only by students but also by teachers. The skills to be developed by a university teacher currently extend beyond instruction, trying to achieve a significant improvement in the quality of the student's teaching-learning process. From our teaching experience over several years and after assessing the concept of good teaching that you have from different fields, a number of generic competencies that we consider essential training for all teachers who do not have a high level of performance can be highlighted. Among these competencies, we can highlight the interpersonal, communicational, methodological, and technological, emphasizing the assessment capacity, given the importance of a competency-based training and its evaluation competency in this educational context. It's not easy to find experts to provide a significant training for university teachers in each of these competencies. We found some very experienced teachers who put into practice some of these skills but we need specialists in the field for the other skills, sometimes outside of education.